Enterprises' Green Growth Model and Value Chain Reconstruction Theory and Method - Wang, Nengmin; Jiang, Qi.; Jiang, Bin.; He, Zhengwen (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The goal of this book is to improve the ability of enterprises to implement the green growth model and value chain reconstruction. China's environmental development strategies, such as carbon peak emission and carbon neutrality, have created new challenges and requirements for enterprises to "go green." In addition, anti-globalization and the complex dynamic uncertainty caused by COVID-19 have changed the operational environment that enterprises face. The application of new technologies, including the new generation of information technologies and the whole process management technology, provides solutions for the implementation of enterprises' green growth model and value chain reconstruction. Based on China's enterprise management cases, this book reveals the connotative features of enterprises' green growth model and their evolutionary regularities, the overall framework and decision optimization of value chain reconstruction under the green growth model, and the approach to implementing the green growth model and value chain reconstruction. The theoretical framework of the green growth model and value chain reconstruction established in this book has enriched and developed the research results in this field. Cases of enterprises implementing the green growth model can provide references for the green transformation of enterprises and help enterprises appreciate the synergy between sustainability and growth. This book can also serve as a research reference for scholars engaged in the field of sustainable operations, as well as decision-makers and managers of relevant government departments.
Chapter 1. An overview of enterprises' green growth model and value chain reconstruction -- Chapter 2. The formation of enterprises' green growth model -- Chapter 3. The trend of enterprises' green growth model -- Chapter 4. The strategical matching of enterprises' green growth model -- Chapter 5. The reconstruction and innovation of value chain of enterprises' green growth model -- Chapter 6. The network design of enterprises' green growth model -- Chapter 7. The building of value chain and coordination of the membership -- Chapter 8. Green product design and innovation -- Chapter 9. Green product pricing -- Chapter 10. Green procurement and outsourcing -- Chapter 11. Manufacturing and remanufacturing -- Chapter 12. Inventory management -- Chapter 13. Green Logistics -- Chapter 14. Collection and resource recycling -- Chapter 15. Supply disruptions and reconstruction of value chain -- Chapter 16. The organization of reconstruction of value chain -- Chapter 17. Social responsibility management -- Chapter 18. Performance management.
Keywords: Economic development; Power resources; Environmental economics; Sustainability; Business; Asia; Economic Development, Innovation and Growth; Resource and Environmental Economics; Sustainability; Asian Business